Molecularly Characterised Xenograft Tumour Mouse Models: Valuable Tools for Evaluation of New Therapeutic Strategies for Secondary Liver Cancers. (26th January 2009) - Mischek, Daniela; Steinborn, Ralf; Petznek, Helga; Bichler, Christoph; Zatloukal, Kurt; Stürzl, Michael; Günzburg, Walter H.; Hohenadl, Christine
Abstract : To develop and evaluate new therapeutic strategies for the treatment of human cancers, well-characterised preclinical model systems are a prerequisite. To this aim, we have established xenotransplantation mouse models and corresponding cell cultures from surgically obtained secondary human liver tumours. Established xenograft tumours were patho- and immunohistologically characterised, and expression levels of cancer-relevant genes were quantified in paired original and xenograft tumours and the derivative cell cultures applying RT-PCR-based array technology. Most of the characteristic morphological and immunohistochemical features of the original tumours were shown to be maintained. No differences were found concerning expression of genes involved in cell cycle regulation and oncogenesis. Interestingly, cytokine and matrix metalloproteinase encoding genes appeared to be expressed differentially. Thus, the established models are closely reflecting pathohistological and molecular characteristics of the selected human tumours and may therefore provide useful tools for preclinical analyses of new antitumour strategies in vivo.